Relationship between selected socio-demographic and health-related factors with intake of fruits and vegetables among the elderly in Malaysia - Ashari, Asmidawati; Yassin, Zaitun; Tengku Abdul Hamid, Tengku Aizan (Nutrition Society of Malaysia, 2008)
Food intake plays an important role in providing adequate nutrients. Several studies have indicated that diets relatively high in fruits and vegetables are associated with a lower risk of chronic diseases. The objective of this study is to identify the relationship between sociodemographic and health-related variables with intake of fruits and vegetables among older persons aged 60 years and above in Malaysia. The subjects were a representative sample from 13 states and the Federal Territory of Kuala Lumpur. One older person within an available household in selected enumeration blocks was included in the study. Information on demographics, socioeconomic status, and lifestyle characteristics was obtained using a pre-tested questionnaire. The frequency per week of fruits and vegetables intake was obtained through a face-to-face interview. The sample consisted of 2,980 older persons (males = 47.9%; female = 52.1%). The mean age of respondents was 70.46 ± 7.2 years, the majority were Malays (58.3%), married (55.8%), with no formal education (44.5%), with an average monthly income of RM551.02. About 75.3% of the respondents were taking vegetables daily and 38.1% were taking fruits daily. By gender, 51.9% of women and 45.7% of men had daily intake of vegetables, while 50.4% of the women and 48.1% of men reported daily intake of fruits. In terms of health status and other lifestyle variables, 54.2% rated their health as “good”, 53.3% were inactive or sedentary and 17.2% were currently smoking. The results showed a significant association between intake of fruits with age (c2 = 7.077, df = 2, p = 0.029), ethnicity (c2 = 42.23, df = 4, p = 0.000), stratum (c2 = 15.126, df = 1, p = 0.000) and self-rated health (c2 = 16.31, df = 3, p = 0.001). On the other hand, only ethnicity (c2 = 11.352, df = 4, p = 0.023) and self-rated health (c2 = 16.16, df = 3, p = 0.001) were significantly associated with intake of vegetables. These findings indicate that there is a relationship between pattern of fruits and vegetables intake with selected demographic and health-related characteristics of the respondents. Therefore, appropriate nutrition intervention programs need to be formulated to encourage increased intake of fruits and vegetables among the elderly in Malaysia to promote optimal health and wellness.